The dynamic systemic immuno-inflammatory index: a novel predictor of neoadjuvant chemotherapy response and outcome in high-risk pediatric neuroblastoma - Zhang, Chenglong; Wang, Xiaoyu; Niu, Huizhong; Zhang, Pengju; Geng, Jianlei (Frontiers in Oncology, 2025)
BackgroundHigh-risk neuroblastoma (HR-NB) has a high mortality rate and a long-term survival rate below 50%. Neoadjuvant chemotherapy (NAC) is essential for HR-NB treatment. However, real-time treatment response biomarkers are lacking. The Systemic Immune-Inflammation Index (SII) shows promise as a prognostic tool for various malignancies. This study explored the relationship between dynamic SII changes during NAC and treatment responses and prognosis in HR-NB.MethodsThis retrospective study analyzed 50 HR-NB patients’ clinical data from January 2013 to November 2024. Peripheral blood samples were collected before and after each cycle of neoadjuvant chemotherapy (NAC) to calculate SII values.ResultsSignificant differences in SII changes were found among treatment response groups (P < 0.05). Spearman analysis showed a strong positive correlation between ΔSII and tumor diameter change rate (r = 0.606, P < 0.001). Regression analyses indicated ΔSII was an independent predictor of tumor diameter change (β = 0.07, 95% CI: 0.05-0.10, P < 0.001) and chemosensitivity (OR = 0.00, 95% CI: 0.00-0.03, P = 0.010). ΔSII was also an independent prognostic factor for EFS and OS (HR = 1.35 and 1.41, P < 0.05) with high predictive accuracy (AUC: 0.766-0.932).ConclusionDynamic SII changes during NAC are significantly linked to treatment response and prognosis in HR-NB, offering a new perspective for precision treatment and prognosis evaluation.